2016
DOI: 10.1039/c5cc10240e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of microbial cells using magnetic focus enhanced lateral flow sensors

Abstract: We report on an improved lateral flow immunoassay (LFIA) sensor with a magnetic focus for ultrasensitive naked-eye detection of pathogenic microorganisms at a near single cell limit without any pre-enrichment steps, by allowing the magnetic probes to focus the labelled pathogens to the target zone of the LF strip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…To confirm the effect of magnetic forces on retarding the movement of particles along the membrane, the particle transit time in a 6-cm unmodified Whatman FF80HP membrane (from sample application to visually-observed arrival of particles at the absorbent pad) was measured in the presence and absence of the magnetic field. Without the magnetic field, the transit took 22 ± 2 minutes (n = 3); When the electromagnets were applied (10-second on/10-second off pulses at 14 V, 0.03 Tesla field strength, electromagnets at top upstream and bottom midstream positions in unsynchronized mode) the transit time increased from 22 to 28 ± 2 minutes (n = 3), confirming that electromagnets can retard the movement of the particles, as previously suggested [ 28 ].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…To confirm the effect of magnetic forces on retarding the movement of particles along the membrane, the particle transit time in a 6-cm unmodified Whatman FF80HP membrane (from sample application to visually-observed arrival of particles at the absorbent pad) was measured in the presence and absence of the magnetic field. Without the magnetic field, the transit took 22 ± 2 minutes (n = 3); When the electromagnets were applied (10-second on/10-second off pulses at 14 V, 0.03 Tesla field strength, electromagnets at top upstream and bottom midstream positions in unsynchronized mode) the transit time increased from 22 to 28 ± 2 minutes (n = 3), confirming that electromagnets can retard the movement of the particles, as previously suggested [ 28 ].…”
Section: Resultssupporting
confidence: 77%
“…Recently Ren et al . (2016) demonstrated that the limit of detection (LoD) of an LFA using magnetic particle reporters could be improved by positioning a permanent magnet under the test line, and suggested that this was because of a longer target-capture line interaction time, leading to increased reporter capture at the detection zone [ 28 ]. It also has previously been shown that delaying the sample flow in gold particle LFAs using strips with incorporated hydrophobic barriers [ 29 ] or focusing target-gold reporter complexes into a thin band and transporting them to the test line using isotachophoresis [ 30 ] can improve the LoD of gold particle LFAs.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli O157:H7 as the most common shiga toxin enterotoxigenic (STEC) foodborne pathogen serves as a model for proof of concept, resulting in a state of the art with remarkable improvement over the years gaining more sensitivity, and specificity by taking advantage of novel nanomaterial properties and alternative capture biomolecules. Recent reports of lateral flow modifications excel with enhanced response detecting concentrations as low as 537 colony forming units (CFU) mL −1 in ground beef by using immunochromatographic assay with gold nanoparticle‐assisted enzyme signal amplification, 200 CFU mL −1 (in pineapple juice) by immunomagnetic sample concentration, and 100 CFU mL −1 (in phosphate buffer) using a traditional lateral flow assay with controlled size and dispersion of the gold nanoparticles . When the complexity of the real food matrix tested increases, the limit of detection (LOD) tends to dramatically decrease due to the noise to signal ratio, posing an obstacle for validation under real conditions; In 2017, Jin and collaborators presented gold decorated polystyrene beads as a novel label material for immunocapture, achieving a limit of detection of 500 CFU mL −1 in ground beef without enrichment …”
Section: Introductionmentioning
confidence: 99%
“…Until now, biosensors based on various analytical techniques and strategies have been reported with improved detection sensitivity. [1][2][3][4][5][6][7][8] However, due to the limited detection capability in large volume samples, there is still a big gap between the reported sensitivity and the regulatory requirement. To bridge the gap, steps to enrich bacteria from samples is usually performed using methods such as culturing, filtration and concentration with NPs.…”
Section: Introductionmentioning
confidence: 99%